A new Bat-Voiced species of Dendropsophus Fitzinger, 1843 (Anura, Hylidae) from the Amazon Basin, Brazil - Orrico, Victor G. D.; Peloso, Pedro L. V.; Sturaro, Marcelo J.; Silva-Filho, Heriberto F. da; Neckel-Oliveira, Selvino; Gordo, Marcelo; Faivovich, Julian; Haddad, Celio F. B. [UNESP] (Magnolia Press, 2014)
We describe Dendropsophus ozzyi sp. nov., a new species of treefrog, tentatively included in the Dendropsophus microcephalus Group and most notably diagnosed by the presence of pointed fingers and an advertisement call with a very high dominant frequency. The new species is known from three localities in the Brazilian Amazon forest, two on western State of Para and one (the type locality) in eastern State of Amazonas (03 degrees 56'50 '' S and 58 degrees 26'36 '' W, 45 m a.s.l.).
Keywords: Advertisement call; Amazonia; Dendropsophini; Dendropsophus microcephalus Group; taxonomy